Aptamer Inhibits Tumor Growth by Leveraging Cellular Proteasomal Degradation System to Degrade c‐Met in Mice. (7th December 2022) - Chen, Kun; Cai, Jiamin; Wang, Sujuan; Li, Yingying; Yang, Chan; Fu, Ting; Zhao, Zilong; Zhang, Xiaobing; Tan, Weihong
Abstract: Current action mechanisms for aptamer‐based therapeutics depend on occupancy‐driven pharmacology to mediate protein functions. We report a new mechanism where aptamers leverage cellular proteasomal degradation system to degrade proteins for cancer treatment. A DNA aptamer (hereinafter referred to as c‐Met‐Ap) binds to the extracellular domain of mesenchymal‐epithelial transition factor (c‐Met) and selectively induces c‐Met phosphorylation at Y1003 and Y1349. The phosphorylation of Y1003 recruits E3 ubiquitin ligase casitas B‐lineage lymphoma, causing c‐Met ubiquitination and degradation in the proteasome. Furthermore, c‐Met‐Ap can induce a decrease in the heterodimeric partner proteins of c‐Met and the downstream effector proteins in the c‐Met signal axis, effectively inhibiting tumor growth in A549 tumor‐bearing BALB/c mice. Our study uncovers a novel, actionable mechanism for aptamer therapeutics and opens a new avenue for developing highly efficient anticancer drugs. Abstract : We report a new mechanism where aptamer leverages cellular proteasomal degradation system to degrade protein for cancer treatment. A DNA aptamer binds to extracellular domain of mesenchymal‐epithelial transition factor (c‐Met), and induces c‐Met phosphorylation at Y1003 and Y1349. The phosphorylation of Y1003 recruits the E3 ubiquitin ligase casitas B‐lineage lymphoma (c‐cbl), which causes c‐Met ubiquitination and degradation in proteasome.